Prophylactic infusion of phenylephrine is effective in attenuating the decrease in regional cerebral blood volume and oxygenation during spinal anesthesia for cesarean section. (February 2019) - Hirose, N.; Kondo, Y.; Maeda, T.; Matsui, M.; Matsuda, M.; Suzuki, T.
Graphical abstract: Phenylephrine infusion is effective in attenuating the decrease in maternal regional cerebral blood volume (rCBV) and oxygenation (rCBO) estimated from near infrared spectroscopy variables during spinal anesthesia for cesarean section. TOI: tissue oxygenation index. Highlights: We evaluated maternal cerebral circulation during anesthesia for cesarean section. Regional cerebral blood volume and oxygenation reduced after spinal injection. Phenylephrine infusion maintained regional cerebral blood volume and oxygenation. Abstract: Background: Hypotension induced by spinal anesthesia for cesarean section causes a decrease in maternal regional cerebral blood volume and oxygenation. We used near-infrared spectroscopy to determine whether prophylactic infusion of phenylephrine attenuates these decreases. Methods: Sixty patients undergoing bupivacaine spinal anesthesia for cesarean section were randomly divided into one of three intravenous infusion groups: saline (P0), phenylephrine 25 (P25) or 50 µg/min (P50). Mean arterial pressure, heart rate and near-infrared spectroscopy measurements were made at one-minute intervals for 20 minutes, and oxyhemoglobin, deoxy-hemoglobin and total-hemoglobin concentrations and tissue oxygenation index were determined. Mean changes in the values between baseline and each measurement time after intrathecal injection were compared. Results: Significant decreases in mean arterial pressure were seen in group P0 compared to P25 and P50 ( P  <0.01). Heart rate decreased in a dose-dependent manner during phenylephrine infusion (P0 vs. P25 and P50, P25 vs. P50; P  <0.05). Significantly higher total-hemoglobin levels were observed in the phenylephrine groups versus the P0 group ( P  <0.01). The largest decrease in tissue oxygenation index was found in the P50, followed by P0 and P25 groups (P0 vs. P25 and P50, P25 vs. P50; P  <0.05). Conclusion: Prophylactic infusion of phenylephrine, especially at 25 µg/min, can effectively suppress decreases in regional cerebral blood volume and regional cerebral blood oxygenation after induction of spinal anesthesia for cesarean section.